High performance control of a three-phase PWM rectifier using odd harmonic high order repetitive control (2016)
The control goal for three-phase pulse width-modulated rectifiers focuses on generating sinusoidal input currents and regulating the DC output voltage. Despite the fact that control strategies such as resonant and repetitive control have been proposed in recent works, with many notable results on the area, they have significant performance decay when the frequency changes in the exogenous signal. In this paper, it is shown that the use of an Odd Harmonic High Order Repetitive Controller can be used to control the three-phase rectifier current loops with a performance that is considerably superior to traditional alternatives developed in this field. This compensator’s Odd Harmonic property keeps a computational complexity similar to that of the conventional repetitive controllers but it has the advantage of increasing the robustness when the signal frequency varies. Simulation and experimental results show the high performance that was obtained even in the case of deviation of network frequency from its nominal value.